The discovery of Fibonacci in integrated communication - Dalmé Mulder (Communicare)
Fibonacci was a renowned scientific explorer. It is widely documented that the famous Fibonacci numbering sequence is found in several spheres of life. To date, this phenomenon has not been discussed within a communication context. However, a literature review done to explore the different functional fields of organisational communication within an integrated communication ideology, has brought to light that the Fibonacci phenomenon might also have relevance in the field of communication. In this article communication - as foundation of modern organisations - is explored from a systems perspective. The position of each of the different functional areas of organisational communication in an organisation practising integrated communication is demonstrated and the resemblance between this demonstration and the Fibonacci swirl is highlighted.